Plasma Type I IFN Protein Concentrations in Human Tuberculosis - Llibre, Alba; Bilek, Nicole; Bondet, Vincent; Darboe, Fatoumatta; Mbandi, Stanley Kimbung; Penn-Nicholson, Adam; Hatherill, Mark; Rozenberg, Flore; Scriba, Thomas J.; Duffy, Darragh (Frontiers in Cellular and Infection Microbiology, 2019)
Tuberculosis (TB) remains one of the leading causes of mortality worldwide, and a lack of understanding of basic disease pathogenesis is hampering development of new vaccines and treatments. Multiple studies have previously established a role for type I interferon (IFN) in TB disease. Type I IFNs are critical immune mediators for host responses to viral infection, yet their specific influence in bacterial infection remains unclear. As IFN-stimulated genes (ISGs) can have both stimulatory and inhibitory effects on immune function, clarifying the role of type I interferon in TB remains an important question. The quantification of interferon proteins in the circulation of patients has been restricted until the recent development of digital ELISA. To test the hypothesis that patients with active TB disease have elevated circulating type I IFN we quantified plasma IFNα and β proteins with Simoa digital ELISA in patients with active disease and asymptomatic M. tuberculosis infection. Strikingly no differences were observed between these two groups, while plasma from acute influenza infection revealed significantly higher plasma levels of both IFNα and IFNβ proteins. These results suggest a discordance between ISG mRNA expression by blood leukocytes and circulating type I IFN in TB.